Epigenetic induction of CD1d expression primes lung cancer cells for killing by invariant natural killer T cells. (3rd June 2018) - Dockry, Éilis; O'Leary, Seónadh; Gleeson, Laura E.; Lyons, Judith; Keane, Joseph; Gray, Steven G.; Doherty, Derek G.
ABSTRACT: Immunotherapies that target CD1d-restricted invariant NKT (iNKT) cells can prevent tumor growth in murine models but trials in humans have shown limited clinical efficacy. Here, we show that iNKT cells are depleted from blood and bronchial lavage samples from patients with non-small cell lung cancer (NSCLC) suggesting a role for these cells in immunity against NSCLC. We interrogated the Lung Cancer Explorer and Kaplan-Meier Plotter databases of NSCLC patients and found that pulmonary CD1d expression is reduced in patients with NSCLC and that low expression of CD1d mRNA is significantly associated with poor patient survival. We hypothesized that CD1d expression in NSCLC is epigenetically regulated and can be modulated using epigenetic targeting therapies. Treatment of the CD1d-negative NSCLC cell lines, A549 and SK-MES-1, with DNA methyltransferase inhibitors and histone deacetylase inhibitors resulted in a dose-dependent induction of CD1d mRNA and protein expression. Chromatin immunoprecipitation analysis indicated that this induction of CD1d expression directly involved chromatin remodelling. Induction of CD1d expression by A549 and SK-MES-1 cells using therapeutic low doses of DNA methyltransferase inhibitors and histone deacetylase inhibitors made them targets for iNKT cell-mediated cytolytic degranulation. Thus, epigenetic manipulation of CD1d expression may augment the efficacy of iNKT cell-based immunotherapies for NSCLC.